Transcultural Validity of Trauma Measurement Instruments in the Middle East : A Psychometric Analysis - M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar; Nurzahara Sihombing (Calory Journal Medical Laboratory Journal, 2025)
This meta-analytic study systematically examines the transcultural validity and psychometric characteristics of various instruments employed to measure psychological trauma in the Middle East. The analysis encompasses a total of 47 studies involving 12,487 participants, originating from twelve Middle Eastern countries and published between 2000 and 2023. Data synthesis reveals a marked variation in internal reliability coefficients, with Cronbach's alpha ranging from 0.73 to 0.92, and construct validity values spanning from 0.65 to 0.87. Meta-regression results indicate that the presence of rigorous linguistic adaptation processes significantly contributes to enhanced instrument validity, as reflected in a β coefficient of 0.43 with a significance level of p less than 0.001. Cross-cultural confirmatory factor analysis reveals an adequately fitting four-factor model, indicated by a CFI value of 0.92 and an RMSEA of 0.058. Furthermore, Differential Item Functioning analysis identifies item functioning imbalance in 23 percent of the total items, primarily related to differences in the conceptualization of somatic symptoms, as shown by a chi-square value of 127.84 and p less than 0.001. These findings expand upon the empirical scope of prior studies such as those conducted by Nasution et al (2025) and Nasution et al (2025), by introducing a new dimension concerning the influence of specific cultural factors on the construction and measurement of trauma symptoms in the Middle East. Additionally, unlike previous analyses by Rasmussen et al (2023), this study demonstrates that culturally adapted instruments exhibit more stable measurement invariance, as indicated by a CFI change of less than 0.01, compared to instruments that are merely translated literally. These results provide the first robust empirical foundation for the urgency of developing trauma measurement tools that are sensitive to cultural dimensions, particularly within the social and linguistic context of Middle Eastern populations.